Development of equipment for welding pipes made of fluoroplast-4D - V. A. Sokolov; N. B. Salykov; A. V. Sedikova (Омский научный вестник)
The description of the installation developed for overlap welding of tube shells of fluoroplast-4D used in the equipment of chemical and petrochemical industries is presented. The results of research of the technological process with application of bounding thermal expansion of internal and external mandrels, and also recommendations for the choice of welding modes are given.